Proceedings 2000 ICRA. Millennium Conference. IEEE International Conference on Robotics and Automation. Symposia Proceedings (C
DOI: 10.1109/robot.2000.846406
|View full text |Cite
|
Sign up to set email alerts
|

Data association for mobile robot navigation: a graph theoretic approach

Abstract: Data association is the process of relating features observed in the environment to features viewed previously or to features in a map. Correct feature association is essential for mobile robot navigation as it allows the robot to determine its location relative to the features it observes. This paper presents a graph theoretic method that is applicable to data association problems where the features are observed via a batch process. Batch observations (e.g., scanning laser, radar, video) detect a set of featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 12 publications
0
82
0
Order By: Relevance
“…During the early 2000's, along with new understanding of using information rather than covariance representations, graph based description of SLAM became started becoming more popular, for example Bailey [12]. The pivotal factor graph representation was described by Kschischang et al [129] in 2001.…”
Section: The Factor Graph Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the early 2000's, along with new understanding of using information rather than covariance representations, graph based description of SLAM became started becoming more popular, for example Bailey [12]. The pivotal factor graph representation was described by Kschischang et al [129] in 2001.…”
Section: The Factor Graph Representationmentioning
confidence: 99%
“…Using Mathematica, we perform the symbolic computations to find the actual message belief 12) which is shown in Fig. 6-9.…”
Section: Leaf Clique Marginalmentioning
confidence: 99%
“…Other popular method is the Joint Compatibility Branch and Bound (JCBB) [18], which considers the compatibility of many associations simultaneously. The Combined Constraint Data Association [2] builds a graph where the nodes are individually compatible associations and the edges relate binary compatible assignments. Over this graph, a Maximal Common Subgraph problem is solved for finding the maximum clique in the graph.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported solutions to the first location using geometrical information gathered by a 2D laser scanner [1], [2], [3]. Our contribution is to combine this laser geometrical information with vision because cameras gather rich photometric information that can solve geometrical ambiguities.…”
Section: Introductionmentioning
confidence: 99%